Maternal Perception of Child Feeds With Medicinal Value in Marsabit County, Kenya - Chepkorir, Rose; Onyango, Agatha Christine; Masinde, David; Musita, Caroline Patricia (European Scientific Journal, ESJ, 2024)
Medicinal foods are important for enhancing children’s health and preventing common illnesses. However, there is a lack of comprehensive understanding regarding how mothers perceive these foods and their effectiveness in child nutrition. Therefore, this study aimed to determine maternal perception of medicinal foods used in child feeding. This study adopted a cross-sectional study design. Three-stage sampling technique was used to randomly select 278 eligible households with children aged 6-24 months, for assessment of their perception of child feeds with medicinal value. A questionnaire was used to gather quantitative data. Focus Group Discussion and Key Informant Interview guides were used to collect qualitative data. Univariate analysis was used to obtain the frequency distribution of maternal perception of medicinal foods. The study concludes that maternal perception of medicinal foods has a significant effect on child-feeding practices in Marsabit County, Kenya. Based on the findings, the study recommends that the Marsabit County government conduct scientific research and clinical trials to assess the efficacy and safety of local plants, fruits, and foods used by mothers to treat childhood illnesses and integrate evidence-based findings into community health education. This initiative should involve collaboration between the local health authorities, research institutions, and traditional knowledge holders.